TECTONIC EVOLUTION OF THE SOUTHWESTERN WALL OF THE BAIKAL RIFT ZONE - Fedotov A.P.; De Batist M.; Pouls T. (My University, 2006)
We investigated the evolution of the southwestern wall of the Baikal Rift Zone (BRZ) based on the seismic structure of the sedimentary cover beneath Lake Khubsugul (Mongolia), a marginal member of the BRZ. The Khubsugul Depression formed along the boundary between the Riphean Tuva–Mongol microcontinent and the Early Paleozoic mobile zone. The Khubsugul Depression is a semigraben with steep western and gentle eastern walls. At present, the depression represents a lake with an average depth of approximately 140 m.
Keywords: Baikal Rift Zone